Influence of Self-efficacy and Motivation on ICT Integration Practice among Teachers in Imo East Senatorial District, Imo State, Nigeria - Obi, Sabina Nwakaego; Berkhout-Nwaobi, Tona Amaka (Universitas Islam Bunga Bangsa Cirebon, 2025)
The persistent underutilization of Information and Communication Technology (ICT) in classroom instruction remains a critical challenge in education, particularly as global standards increasingly demand digital proficiency. This study investigated the extent to which self-efficacy and motivation influence ICT integration practices among secondary school teachers. The objective was to determine the joint and relative contributions of these psychological and motivational factors to teachers' use of ICT in instruction. A descriptive survey research design was adopted. The population comprised 3,786 public secondary school teachers, of which 398 were selected using simple random sampling across 27 schools in nine local government areas. Data were collected using three validated instruments: the General Self-Efficacy Scale (α = .87), Motivation Scale (α = .78), and ICT Integration Practice Scale (α = .73). Multiple regression analysis revealed a significant joint influence of self-efficacy and motivation on ICT integration (F(2,394) = 21.974, Adj. R² = .771, p < .05), accounting for 77.1% of the variance. Motivation (β = .481) had a slightly stronger predictive power than self-efficacy (β = .426). The study concluded that while teacher confidence is crucial, consistent motivation through training and institutional support plays a more dominant role in facilitating ICT adoption. These findings contribute to educational psychology and technology adoption literature by emphasising the need for capacity-building strategies that address both the psychological readiness and professional development of teachers. Educational stakeholders must prioritise both empowerment and support structures to bridge the gap in ICT integration and improve instructional quality.